PENGARUH PENGGUNAAN APLIKASI QUIZIZZ SEBAGAI ALAT EVALUASI PEMBELAJARAN FISIKA - Rudi Haryadi; Riza Nurmala (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study is to describe the implementation of Village Regulation No. 4 of 2019 concerning Traditional Money in Koto Dua Baru Village, Air Hangat Barat District, Kerinci Regency. This research is a qualitative research using descriptive method. The results of this study indicate that the implementation of village regulations regarding customary money has not been carried out optimally because there are regulatory violations committed by the community and there are obstacles in the implementation of Village Regulation No. 4 of 2019 concerning Customary Money in Koto Dua Baru Village, Air Hangat Barat District, Kerinci Regency.